Analytical Solutions for a Horizontally Oscillated Semi-Submerged Cylinder (Global Journal of Science Frontier Research, 2017)
The Krylov-Bogoliubov-Mitropolskii (KBM) method is an enormously used technique to study the transient behavior of vibrating systems. In this work, an oscillating semi-submerged horizontal cylinder is considered in a liquid and the governing equation of this system deem to weakly nonlinear to find out the solutions. Analytical approximate solutions are investigated for obtaining the transient response of the system for undamped and damped oscillatory motions. The results obtained by the proposed technique for the different sets of initial conditions have found to be well suited with the numerical solutions.
Keywords: asymptotic and perturbation solution; nonlinearity; oscillatory damped and undamped system; gravitational force; semi-submerged cylinder